SUCCESS STRATEGIES TO STRENGTHEN PERSONAL BRANDING ON SOCIAL MEDIA - I Made Pasek Bhajraskara Suryatmaja; I Nengah Dasi Astawa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
In this digital era, social media is growing very rapidly. Social media allows people to easily obtain, manage, and disseminate information. The use of social media is a new way to improve Personal Branding. Strengthening personal Branding is one of many ways to increase a person's or company's value or outlook. The Bali Institute of Design and Business is a private university in design and business that is integrated into the local Balinese culture. Being a private university is a challenge; you have to compete with private and public universities every year to attract prospective students. This study aims to explore the personal branding success strategies that IDB Bali has implemented on social media in depth. First, researchers use the concept and characteristics of Personal Branding. Then the research method used is descriptive qualitative and data collection techniques are interviews and documentation conducted with IDB Bali staff. The description in the study found that to strengthen personal Branding, IDB focused on the content and needs of followers on social media and prospective students interested in learning or going deeper into the world of design and business. The shared content is always blue and slightly orange with an up-to-date design. As the name implies a design and business campus, they always show the design and business side of every content and activity that is used as content on social media. Then since they were founded as a design school, they have a rule that staff and students must re-share IDB Bali content on social media daily.